Sustainability of Smallholder Oil Palm Plantations: A Multidimensional Scaling (MDS) Approach in North Konawe Regency, Indonesia - Yusuf, La Ode Muhammad Iksan; Nabila, Asma; Rahim, Abd; Erwin, Erwin; Hastuti, Diah Retno Dwi (Jurnal Agrikultura, 2026)
Smallholder oil palm plantations play a strategic role in supporting local livelihoods and the national supply chain. In North Konawe Regency, this sector is a cornerstone of the regional economy, making its sustainability critical amid environmental challenges and market fluctuations. Current palm oil studies are predominantly focused on large-scale industries and often lack an integrated, multidimensional approach encompassing economic, ecological, institutional, and socio-cultural dimensions, particularly in the context of Southeast Sulawesi. This study aims to assess the multidimensional sustainability status and identify sensitive attributes influencing the resilience of smallholder plantations. Research was conducted from April to July 2025, involving 124 farmers and nine farmer groups. Data were analyzed using the Rapid Appraisal for Palm Oil (RAPPO) method based on Multidimensional Scaling (MDS) and leverage analysis. The results reveal a sustainability index of 66.01%, categorized as fairly sustainable. The institutional dimension achieved the highest score (70.00%), followed by ecology (67.80%), economy (67.72%), and socio-cultural (58.48%). Leverage analysis identified key sensitive attributes: flora and fauna diversity (ecology), economic benefits for local communities (economy), certification implementation (institutional), and the frequency of inter-farmer conflicts (socio-cultural). This study contributes to the literature by providing an integrated sustainability profile of smallholder plantations in North Konawe. The implications underscore the need to strengthen farmer institutions and synchronize input subsidy policies to ensure the economic stability of smallholders while maintaining environmental integrity.